FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PENGGUNA E-WALLET TERHADAP INTENSI PERILAKU PADA SISWA DI KOTA BATAM - Gomes, Muhammad Nunu; Wangdra, Ronald (Universitas Putera Batam, 2024)
The main objective of this research is to foster innovation and the advancement of new technologies. This is achieved through understanding the needs and challenges faced by potential users of these technologies. The study focuses on technology adoption factors like effort expectancy, hedonic motivation, and price values, and how they influence the behavioral intentions of student research subjects in several universities located in Batam City. To gather data, the researchers employed a random sampling probability technique, and data collection was done using an online questionnaire based on Google Forms. The survey was distributed across various campuses in Batam, and the sample size consisted of 100 respondents, determined using the Slovin formula. The analysis utilized descriptive analysis, incorporating multiple linear regression tests, t-tests, f-tests, and determinations. The findings of the study indicate that the effort expectancy variable positively and significantly influences the behavioral intentions of students in Batam City. Similarly, the hedonic motivation variable also positively and significantly impacts the behavioral intentions of students in the same area. However, the price value variable has a negative and significant effect on the behavioral intention of students in Batam City.